G20 INDONESIA 2022: A MULTIMODAL DISCOURSE ANALYSIS IN BANK INDONESIA’S DIGITAL FLYER - Vivi Sitinjak; Bernardus Ginting; Asima Tamba; Mega Manalu; Anna Samosir (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
The discursive construction of G20 in Indonesia in this current digital communication era is no longer dominated by the elite’s discourse. Social media allows the common people to also express their conception of G20 in Indonesia. This article aims to explain how Indonesia is being portrayed as a unified nation that consists of various cultural and social groups. Additionally, the purpose of this article is to provide insights whether social media, particularly Instagram, have a meaningful role in maintaining, countering, or even altering the elite’s conception of Indonesia national identity. The data for this article consists of the visual and textual data collected from Bank Indonesia’s G20 flyer. By implementing multimodal discourse analysis, this study investigates the visual and textual narration of Bank Indonesia’s G20 flyer. Utilizing multimodal discourse analysis in this study became crucial because through investigating the rich multimodal data. The writers using descriptive qualitative research to engage the multimodal discourse analysis in G20 flyer by Bank Indonesia for welcoming and enliven the summit. The writers used multimodal discourse analysis in order to interpret the meaning from elements in the G20 flyer by Bank Indonesia. The data that containing in this analysis are categorized as verbal and non-verbal texts. The verbal text data were words, phrases, and clauses. The non-verbal data were logo, pictures, symbol/emblem, and color. Referring to Social Identity Theory, the study found that the digital flyer is built upon the construction of positive self-representation of the in-group members which revolved around the G20 summit. The discourse is dominated by the social groups related by G20 summit in the public discourse. However, one significant pattern can be identified in this data is that the populist discourse in Indonesia, was initiated by the people that able to change the political leader’s discourse to adjust with the people’s expectation. These findings indicate the importance of utilizing to analyse the holistic and nuance conception of identity representation. In addition, this study also highlights the important role of social media as the people’s communication platform to counter balance the elite’s political discourse.Keyword: Digital Flyer; G20 Indonesia Flyer; Multimodal Discourse Analysis